PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, DISIPLIN KERJA, TERHADAP KINERJA GURU SD DI WILAYAH KECAMATAN KLATEN SELATAN KABUPATEN KLATEN - Tukiyo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the influence of the principal's leadership and work discipline on elementary school teachers’ performance in Kecamatan Klaten Selatan, Kabupaten Klaten. The method used in this study was a survey. The target in this study were elementary school teachers in Kecamatan Klaten Selatan, Kabupaten Klaten. The analysis technique in this study used the classical assumption test, multiple linear regression method, hypothesis testing and coefficient of determination test. The results of the study were that there was a positive and significant influence on principal leadership and work discipline on teachers’ performance with a determination value of 49.1%. This means that the influence of the principal's leadership and teachers’ work discipline on the performance of elementary school teachers in Kecamatan Klaten Selatan, Kabupaten Klaten. was explained by 49.1% while 50.9% was influenced by other variables. From the results of the t-test, this research concluded that the principal's leadership variable had a partial correlation coefficient of 0.146, the t-count value of 1.846 and a significance value of 0.067>0.05, then partially the hypothesis which read that there was a positive and significant influence between the principal's leadership on teachers’ performance Elementary schools in the Education Coordinator of Kecamatan Klaten Selatan, Kabupaten Klaten.